Preparation of MS2 Phage-Like Particles and Their Use As Potential Process Control Viruses for Detection and Quantification of Enteric RNA Viruses in Different Matrices - Mikel, Pavel; Vasickova, Petra; Tesarik, Radek; Malenovska, Hana; Kulich, Pavel; Vesely, Tomas; Kralik, Petr (Frontiers in Microbiology, 2016)
The detection and quantification of enteric RNA viruses is based on isolation of viral RNA from the sample followed by quantitative reverse transcription polymerase chain reaction (RT-qPCR). To control the whole process of analysis and in order to guarantee the validity and reliability of results, process control viruses (PCV) are used. The present article describes the process of preparation and use of such PCV– MS2 phage-like particles (MS2 PLP) – in RT-qPCR detection and quantification of enteric RNA viruses. The MS2 PLP were derived from bacteriophage MS2 carrying a unique and specific de novo-constructed RNA target sequence originating from the DNA of two extinct species. The amount of prepared MS2 particles was quantified using four independent methods - UV spectrophotometry, fluorimetry, transmission electron microscopy (TEM) and a specifically developed duplex RT-qPCR. To evaluate the usefulness of MS2 PLP in routine diagnostics different matrices known to harbor enteric RNA viruses (swab samples, liver tissue, serum, feces, and vegetables) were artificially contaminated with specific amounts of MS2 PLP. The extraction efficiencies were calculated for each individual matrix. The prepared particles fulfill all requirements for PCV – they are very stable, non-infectious, and are genetically distinct from the target RNA viruses. Due to these properties they represent a good morphological and physiochemical model. The use of MS2 PLP as a PCV in detection and quantification of enteric RNA viruses was evaluated in different types of matrices.